An archive of humanity: the NSW Division of the Australian Red Cross, 1914–2014. Issue 2 (4th May 2019) - Wishart, Alison; Carney, Michael
ABSTRACT: To commemorate its centenary, the NSW Division of the Australian Red Cross decided to donate its archive to the State Library of New South Wales in 2014. The State Library is honoured to be the recipient of these significant and extensive archives. In this article, the authors outline the process the librarians and archivists used to manage the donation and the importance of communication, both internally within the Library, and externally with the volunteers at the Red Cross who had arranged, compiled and cared for the archive. They describe the extent and organisation of the collection, the variety of formats and subjects, its historical significance and how it has been promoted to the State Library's audiences. The authors reflect on how the archive charts the evolution and growth of Australia's longest-running humanitarian organisation and how it contains the records of people who made history, but did not write the history books.